Chagas disease treatment efficacy markers: experiences from a Phase III study with nifurtimox in children - Grossmann, Ulrike; Rodriguez, Maria-Luisa (Frontiers in Parasitology, 2023)
Determining the success of antitrypanosomal therapy for Chagas disease is challenging, particularly in the chronic phase of the disease, because seropositivity persists for a long time after successful antitrypanosomal treatment and is known to be related to the duration of Trypanosoma cruzi infection. Seroconversion to negative by two or more conventional serologic tests is the currently accepted measure of efficacy, and studies suggest no significant change in seropositivity if left untreated. However, there is no guidance for industry on how to establish the effectiveness of drugs intended for the treatment of Chagas disease. Due to the lack of validated sensitive, specific, easy-to-use markers that allow early monitoring of the efficacy of antitrypanosomal treatment in an efficient manner, we used seroreduction measured by two conventional enzyme-linked immunosorbent assays in addition to the currently accepted criterion for what constitutes a cure, seroconversion to negative, as a surrogate parameter for efficacy in a Phase III pediatric trial with nifurtimox. The measures for confirmation of the antitrypanosomal efficacy of nifurtimox were discussed with US FDA. In this perspective article, we present our experiences obtained from a pediatric study on Chagas disease with an established drug using a surrogate efficacy parameter in addition to the established criterion for a cure.